2010
DOI: 10.1080/15388220903585861
|View full text |Cite
|
Sign up to set email alerts
|

“i h8 u”: The Influence of Normative Beliefs and Hostile Response Selection in Predicting Adolescents' Mobile Phone Aggression—A Pilot Study

Abstract: Mobile phone aggression (MPA) is a relatively new phenomenon.Using newly developed measures, a pilot study was conducted with 348 adolescents ages 13-17 years to determine the incidence of MPA and victimization in this group of adolescents and to test a proposed model in which hostile response selection mediated the relationship between normative beliefs and MPA. Girls reported more incidences of both MPA and victimization; however, the overall frequencies of these were both relatively low. Path analysis revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 52 publications
1
28
0
Order By: Relevance
“…At this level, texting may interfere with the formation of face‐to‐face relationships as much conversation is done in a virtual fashion. Additionally, aggression may be common for “perpetuals,” because it is possible that heavy cell phone users explore and enhance delinquent relationships while isolating others, including parents (Nicol & Fleming, ). Indeed, this group showed the worst relationship with their fathers at the final time point though not mothers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At this level, texting may interfere with the formation of face‐to‐face relationships as much conversation is done in a virtual fashion. Additionally, aggression may be common for “perpetuals,” because it is possible that heavy cell phone users explore and enhance delinquent relationships while isolating others, including parents (Nicol & Fleming, ). Indeed, this group showed the worst relationship with their fathers at the final time point though not mothers.…”
Section: Discussionmentioning
confidence: 99%
“…Cell phone use has also been linked with a number of positive and negative outcomes for adolescents, though again, few studies have examined these relations over time. High levels of texting has been positively associated with depressive symptoms or anxiety (Sánchez‐Martínez & Otero, ), and aggressive behavior (Nicol & Fleming, ). Additionally, a growing number of studies suggest that cell phone use can become problematic and may show similarities with other substance and technological addictions (e.g., Roberts, Petnji Yaya, & Manolis, ).…”
Section: Media Use Across Adolescencementioning
confidence: 99%
“…A growing body of literature indicates that excessive test messaging is related to a variety of negative outcomes, such as depressive symptoms, anxiety, and aggressive behavior (e.g., Nicol & Fleming, 2010;Sánchez-Martínez & Otero, 2008). A recent longitudinal study conducted by Coyne, Padilla-Walker, and Holmgren (2018) revealed that high and stable levels of texting early in adolescence were related to various negative outcomes later.…”
Section: Problematic Text Messaging As a Societal Issuementioning
confidence: 99%
“…In our study, we focus on normative beliefs about aggression, which have been connected to aggressive behavior among children and youth. Previous studies consistently reported that normative beliefs were associated with offline bullying (Burton, Florell & Wygant, ; Cook, Williams, Gendron et al ., ; Guerra, Kim & Sadek, 2010; Guerra, Williams & Sadek, ; Kikas, Peets, Tropp & Hinn, ; Vernberg & Jacobs, ; Werner & Nixon, ) and cyberbullying (Ang, Tan & Mansor, ; Nicol & Fleming, ; Williams & Guerra, ; Wright & Li, ). A meta‐analytic study conducted by Cook et al .…”
Section: Normative Beliefs About Aggressionmentioning
confidence: 99%